(untitled) (Perner’s Contacts, 2019)
The potential of European rivers is currently under-utilized. The EU competent authorities aim to increase the potential of waterways and promote inland navigation as an environmentally friendly mode of transport. EU support programs raise awareness of water use, its use and contribution to EU transport policy. By ensuring transparency in the allocation of competences at international level and by introducing effective financial incentives, it is possible to improve overall governance and support the development of inland waterway transport within the EU.